Analysis of Decentralization in the Central Government's Acquisition of Provincial Road Management - Mitaya, Filicia Vinidya (Jurnal Hukum Magnum Opus, 2024)
Infrastructure is a crucial aspect necessary for a state to perform its various functions. One type of infrastructure that plays a vital role in ensuring the smooth mobility of the general public is roads. Unfortunately, in Indonesia, the quality of road networks cannot be described as ideal. The substandard condition of these roads has drawn public concern, particularly following a social media post by a resident of Lampung Province criticizing the quality of roads there. In response to this public attention, the Central Government decided to assume the duties, authority, and responsibility for repairing 15 (fifteen) roads in Lampung Province. This decision has sparked new concerns among the public regarding the centralization of duties, authority, and responsibilities, which could undermine the spirit of decentralization. Based on the findings presented in this article, it can be asserted that the central government's assumption of the duties, authority, and responsibilities of local governments does not violate prevailing laws and regulations and is in accordance with them. Nevertheless, the phenomenon of the central government taking over these responsibilities warrants attention. This case highlights that the Lampung Provincial Government is not entirely capable of managing the tasks mandated by the Central Government. Therefore, from the findings of this case, it is evident that there is still a significant need for the maturation of Regional Governments in fulfilling the duties, authority, and responsibilities entrusted to them.